The Role Of Students: Perceptions In Modifying Science And Mathematics Classroom Activities - Nannestad, Charles Leif (Curtin University, 2002)
The aim of this study was to provide teachers with a practical means to obtain timely indications of their students reactions to individual activities. Teachers could then modify their presentations of activities cognisant of those students perceptions. The study set out to establish a suitable instrument, and then to evaluate its use by classroom teachers.Five experienced science and mathematics teachers identified five characteristics of interest when considering students perceptions of classroom activities: Understand Content, Communication, Relevancy, Work Output, and Enjoyment. A fifteen-item instrument based upon these characteristics was developed for this study. The viability of the survey for use by busy classroom teachers was increased by the short and succinct format, as well as the provision of a computer graphing template to process and display responses. The combination of the survey and computer template is called the Students' Perceptions of an Activity Instrument and Display (SPAID).Teachers appreciated the provision of a structure to assist their reviewing the use of activities, and the rapidity with which the information was available. Students' responses provided timely support for teachers' decisions to engage classes in the activities and increased teachers' confidence in the worth of the activities. Alterations to activities were small in scale and idiosyncratic to the student cohorts. Teachers' use of the SPAID package was also noted to enhance cooperation with colleagues within the government secondary schools of Brunei Darussalam.